The COD/VSS ratio of the volatile solids in the activated sludge process - Schroeter, Wolfgang Dietrich (Department of Civil Engineering, 2017)
In the kinetic analysis of the activated sludge process behaviour, a vital requirement is that a COD balance near unity is obtained. The COD/VSS ratio of the mixed liquor forms an integral part of such a balance by reason that the practice has arisen, prompted by convenience, to determine the VSS rather than the COD of the mixed liquor and to convert the VSS to COD by accepting a COD/VSS ratio. Evidently good experimental COD recoveries will depend on the correctness of the COD/VSS ratio. Dold, Ekama and Marais (1980), in an analysis on the dynamic behaviour of the aerobic activated sludge process, observed that no COD balances on their experimental data near unity were possible for a 2,5 day and 20 day sludge age at 12°C. They hypothesized that under the conditions above a possible cause for the lack in COD balances was that the COD/VSS ratio was higher than that 'normal' at the longer sludge ages at 20°C i.e. COD/VSS = 1,48 mgCOD.mgVSS⁻¹; then, in a mass balance if the lower value was used the apparent loss of COD recovery would be observed. Such a high COD/VSS ratio could very likely arise from an accumulation of solidified fats (derived from the influent) at the lower temperature i.e. 12°C. Upon solidification, these fats could be relatively resistant to biodegradation thereby leading to a substantial accumulation on the sludge mass. As the average COD/VSS ratio of fats is of the order of 2,6 mgCOD.mgVSS⁻¹ it is clear that, upon accumulation, these could increase the COD/VSS ratio. At 20°C, it was hypothesized that the fats, most probably, are in an emulsified form and therefore amenable to biodegradation; a substantial accumulation of fats is therefore not expected at this temperature. To test the above hypothesis, aerobic activated sludge units at a 20, 8 and 3 day sludge age at 12°C and 20°C treating a raw domestic effluent were operated and tested. These experiments indicated a slight increase in the COD/VSS ratio at a 3 day sludge age at 12°C (relative to the other units) but insufficient to explain the discrepancies in the COD balances observed by Dold et al. (1980). During the above experiments it was established that a significant error (up to 30 percent) in the COD balance can occur due to oxygen transfer from the atmosphere into the liquid mass giving rise to an under estimation of the 'true' oxygen consumption rate of the mixed liquor. By sealing the liquid surface from contact with the atmosphere during an oxygen consumption rate measurement, (particularly at the short sludge ages and low temperatures) good COD recoveries were achieved. It was concluded that the most likely cause for the discrepancies between the observed and predicted response in Dold et al's (1980) experiments was due to this error in the oxygen consumption rate measurement; this was verified by repeating the experiments under the same conditions, after Dold et al. (1980), and obtaining COD mass balances of close to 100 percent. To enquire whether fats could be a significant factor in raising the COD/VSS ratio value above that of 'normal' activated sludge (treating a 'normal' municipal effluent) at the short sludge ages, a set of experiments was inaugurated at a 3 day sludge age at both 12°C and 20°C - two units treating only raw domestic sewage and the other two treating raw domestic sewage spiked with up to 33 percent of influent COD by mass with oleic acid. It was observed that the COD/VSS ratio for the units treating artificially added fat (in the form of oleic acid) increased above the ratio in the units treating only raw domestic sewage thereby indicating that high concentrations of fat can increase the COD/VSS ratio under these conditions. However, with the 'normal' fat concentrations expected in a municipal effluent, the effect on the COD/VSS ratio should be negligible for sludge ages of 3 days and longer between -1 temperatures of 12°C and 20°C; a COD/VSS ratio of 1,48 mgCOD.mgVSS, as proposed by Ekama and Marais (1978) appears to be acceptable for the design of activated sludge processes at 3 days sludge age or longer and temperatures ranging from 12°C to 20°C.